2013
DOI: 10.1002/jip.1407
|View full text |Cite
|
Sign up to set email alerts
|

Offending Patterns of Serial Sex Offenders: Escalation, De‐escalation, and Consistency of Sexually Intrusive and Violent Behaviours

Abstract: A series of stranger sexual assaults poses considerable obstacles for law enforcement officials. One such preoccupation is concerned with whether or not the offender will escalate in the severity of his behaviours with subsequent victims. The current study uses transition matrices to address whether or not the offending patterns of 72 serial stranger sex offenders change from one victim to the next as it pertains to their sexual acts and level of physical force used during the crime. Findings indicate that sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 38 publications
(54 reference statements)
1
21
0
2
Order By: Relevance
“…To be specific, if an offender has used physical force against one victim, then it is less likely that the offender uses a different manner (e.g., seduction strategies) to commit another crime against another victim. This finding is consistent with the behaviors of serial sex offenders in stranger rape cases that they exhibited stable behavioral patterns across all victims (Hewitt & Beauregard, 2014).…”
Section: Offence Scripts Of Sex Offenderssupporting
confidence: 87%
See 4 more Smart Citations
“…To be specific, if an offender has used physical force against one victim, then it is less likely that the offender uses a different manner (e.g., seduction strategies) to commit another crime against another victim. This finding is consistent with the behaviors of serial sex offenders in stranger rape cases that they exhibited stable behavioral patterns across all victims (Hewitt & Beauregard, 2014).…”
Section: Offence Scripts Of Sex Offenderssupporting
confidence: 87%
“…In contrast, Leclerc et al (2009) indicated that aggressive behaviors employed by the victim were likely to increase offender's physical force, which also resulted in more severe injury on victims. In a similar vein, Hewitt and Beauregard (2014) found that victim resistance made offenders employ physical force greater than necessary to subdue their victims.…”
Section: Sexual Fantasymentioning
confidence: 95%
See 3 more Smart Citations